(untitled) (Research, Society and Development, 2021)
The present study aimed to evaluate the physical-hydraulic quality of soils with different years of management after planting Vitis vinifera L. cv. Pinot Noir. Areas with 4, 9 and 16 years of cultivation were evaluated, at depths of 0.0-0.10, 0.10-0.20, 0.20-0.30, 0.30-0.40, 0.40-0.50 and 0.50-0.60 m, in three replicates, in the wheel track (WT), between wheel tracks (BWT) and in the planting row (PR), were analyzed. The physical quality indicators analyzed were bulk density, macroporosity, microporosity, total porosity. Soil water infiltration was also analyzed at these positions, by the method of double concentric rings, both with 30 cm height, and diameters of 50 cm in the outer ring and 25 cm in the inner ring, which were buried 15 cm deep into the soil and filled with water. Soil management in the different periods of planting resulted in a heterogenous soil compaction in the vine interrows. The position between wheel tracks (BWT) has a higher infiltration rate, regardless of the vineyard management time.